Aplikasi sebagai Solusi Alternatif Pengelolaan Keuangan dan Upaya Manajemen Risiko pada BumDes Kemudo Makmur - Aditya Wirawan; Rani Gutomo; Ambang Aries Yudanto (SULUH: Jurnal Abdimas, 2020)
This Community Service Activity has been conducted in the Village-Owned Enterprises (BUMDesa) Kemudo Makmur, Kemudo Village, and Klaten Regency. The purposes of these community service activities are to provide alternative solutions to the BUMDesa’s financial reporting problem and to enhance the awareness toward BUMDesa’s potential risks. “Aplikasi UKM“is offered as an alternative solution to the financial statement problems. Introducing the risks matrix that may provide simple information about the potential raised by BUMDes become the following activity in these community service activities. The community service activities consist of preliminary survey, focused interview, training and consultation.